Progress, clinical application and challenges of non-invasive prenatal testing for monogenic diseases - Wang, Chengcheng; Hou, Dongxia; Wang, Gang; Wu, Xi; Zhou, Zhiyong; Yang, Lina; Liu, Ying; Wang, Xiaohua (Frontiers in Pediatrics, 2026)
Monogenic diseases represent a significant healthcare challenge, characterized by their heritable nature and substantial disease burden. While non-invasive prenatal testing (NIPT) is well-established for aneuploidy, its application has rapidly expanded to monogenic conditions. However, current monogenic NIPT faces challenges including low sensitivity for maternally inherited variants, limited fetal DNA fraction, high cost, lack of standardized clinical validation, and complex ethical and counseling considerations. This review systematically summarizes the major technological approaches, current clinical applications, and core challenges of NIPT for monogenic diseases. It further discusses the underlying scientific issues and translational barriers associated with existing technical limitations, and offers perspectives on future directions. The aim is to provide a reference framework for advancing research and promoting standardized clinical implementation in this field.